Book Review: Socioeconomia fluminense [Socioeconomy of Rio de Janeiro state], by Carlos Antônio Brandão, Deborah Werner, Fábio Lucas Pimentel de Oliveira - Cláudio Zanotelli (Geografares, 2021)
This book originated from discussion meetings of the Grupo de Pesquisa Espaço e Poder [Space and Power Research Group] of Ippur/UFRJ, in which its content was prepared. As the organizers write in the Introduction «(...) it started with an analysis of the crisis situation seen as a moment in which multifaceted social, political, economic and ideological contradictions are condensed and take a specific and distinctive way to think about nature. structure of disruptive changes in the state of Rio de Janeiro. Especially after the Covid-19 pandemic, these moments of complexity, chaos and contradictions were exacerbated in a multi-determined mosaic". The authors seek, therefore, to analyze various themes and the consequences of neoliberalization processes on the territory of Rio de Janeiro state. The authors say that the state of Rio de Janeiro is a paradigmatic case of what happens in Brazil with the implementation of "(...) recurrent rounds of neoliberalization that dismantle public structures and promote a pro-market logic, with the loss of capacity of public action to set up strategies to face its multiple problems".